Faktor-Faktor Yang Mempengaruhi Alih Fungsi Lahan Di Desa Nanjungan - Wira Merina; Yossie Yumiati; Eko Sumartono (SINTA Journal (Science, Technology, and Agricultural), 2023)
This agricultural land has been converted into sustainable agricultural land for corn commodities which caused rice production to experience crop failure due to damage to the river water dam in Nanjungan village causing rice plants to experience drought. The purpose of this study was to compare the income levels of rice farmers before and after planting corn in Nanjungan Village?, to find out what factors influence land conversion? The research method used was the difference in income levels of rice farmers before and after planting corn as indicated by a simple random sample in the research and discussion. income before function transfer Rp. 21,029,148, - Income after land conversion Rp. 31.102.014,-. Factors that affect the conversion of multiple linear regression analysis partially affect price (X_2), income (X_3), while for production (X_1), farming experience (X_4), number of family dependents (X_5) have no significant effect.